Curadoria e prática artística : reflexões sobre a curadoria contemporânea e o trânsito entre as atuações do artista e do curador - Cunha, Clara Sampaio (2016)
The thesis investigates matters related to the emergence, development and challenges of contemporary curation, taking into consideration the transformations undergone by museums and art galleries throughout the decades, mainly due the Modernist Vanguards